Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia - Ahyong, Shane T. (Zootaxa, 2017)
The stomatopods from the Austral and Gambier Islands, southern French Polynesia, collected primarily by the BENTHAUS Expedition (2002) are reported herein. Prior to the present study, only one species of stomatopod, Bathysquilla microps (Manning, 1961), was known from the Austral Islands and two from the Gambier Islands, Gonodactylus chiragra (Fabricius, 1781) and Pseudosquilla ciliata (Fabricius, 1787). Seven of nine species in the present collection are reported for the first time from the area, of which Gonodactylellus rubriguttatus (Erdmann & Manning, 1998) and Odontodactylus hawaiiensis Manning, 1967, are reported for the first time from French Polynesia. The series of specimens of G. rubriguttatus includes the largest known of the species, which also shows significantly longer accessory median carinae of the telson than previously reported. Owing to previous taxonomic instability in Chorisquilla excavata (Miers, 1880), the type species of its genus, it is redescribed based on type and other material.